Peran Musabaqoh Qiroatul Kutub (MQK) Dalam Peningkatan Motivasi Belajar Kitab Kuning Di Pondok Pesantren Fathul Ulum Jombang - Moh. Kholik; Abd Rozaq; Dedi Puspita (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
The purpose of this study is to describe the role of Musabaqoh Qiroatul Kutub (MQK) in increasing motivation to learn the yellow book, which is focused on the implementation of Musabaqoh Qiroatul Kutub (MQK) at the Fathul Ulum Islamic Boarding School Jombang, the motivation to learn the yellow book at the Fathul Ulum Islamic Boarding School Jombang, how the role of Musabaqoh Qiroatul Kutub (MQK) in increasing motivation to learn the yellow book at the Fathul Ulum Islamic Boarding School Sanan Puton Diwek Jombang. This study uses a descriptive qualitative approach, with a case study design of data collection techniques through interviews, observation, and documentation. Furthermore, data analysis was carried out using an interactive analysis model. The results of the study state that: 1. The MQK at the Fathul Ulum Islamic Boarding School is held every 27th Rojab which is carried out in accordance with the implementation and assessment techniques of the Ministry of Religion's MQK, only differing in determining the level and the winner. 2. The motivation to learn the yellow book at the Fathul Ulum Islamic Boarding School is low because it is influenced by interests, talents and thoughts about the times. The strategies applied are a) the development of learning such as learning nature, rihlah and halaqah. b) competitions such as wording in Arabic, quizzes, opening dictionaries, and MQK. 3. The application of Musabaqoh Qiroatul Pole (MQK) at the Fathul Ulum Islamic Boarding School in Jombang plays a very important role in increasing students' motivation to learn the yellow book. The development of a strategy by not eliminating the Islamic tradition in this age of technological development really needs to be done to increase motivation to learn the yellow book, so that the main goal of pesantren, namely to produce generations of good morals and generations of Ulama cadres, can still be achieved.